METODE PEMBELAJARAN KITAB KUNING DI PONDOK PESANTREN DAARUN NAHDHAH THAWALIB BANGKINANG - Ali Akbar; Hidayatullah Ismail (AL-FIKRA, 2018)
This paper discussed about "The Method of Learning of the Yellow Book at Daarun Nahdhah Thawalib Boarding School Bangkinang". The research was conducted with qualitative descriptive approach and the technique data collection was done by interview, documentation, and observation technique. The result of the research showed that the method of learning of the yellow book in Daarun Nahdhah Thawalib Boarding School Bangkinang used mixed method, meaning that sometimes the ustadz / ah who read it actively, while students only hear or read the reading and the explanation of the ustadz / ah. This method is known as the bandongan method. On the contrary, sometimes students are active, meaning students read and translate word by word, while ustadz / ah supervise, assess, and guide students ability maximally in mastery of yellow book material.